Brooklyn nine-nine. Season four [videorecording (DVD)] - Samberg, Andy, 1978-; Beatriz, Stephanie; Crews, Terry, 1968-; Fumero, Melissa, 1982-; Braugher, Andre; Blocker, Dirk, 1957- (Universal Pictures Home Entertainment, 2017)
Follows the adventures of the detectives and their commanding officer in a Brooklyn, New York, police precinct.